Structure-Based Identification of HFS764 as an Inhibitor of the HIF-1α–p300 Interface in Hypoxic Renal Cell Carcinoma - Mesfer Mohammad Al Shahrani (Discovery Medicine, 2026)
Background: Hypoxia-inducible factor-1 alpha (HIF-1α) drives tumor adaptation to hypoxia by promoting angiogenesis, metabolic reprogramming, and survival signaling in clear cell renal cell carcinoma (ccRCC). Transcriptional activity of HIF-1α depends on its interaction with the p300/CBP (CREB-binding protein) coactivator via the C-terminal transactivation domain (C-TAD). Direct targeting of this protein–protein interface remains limited, highlighting the need for novel inhibitors.Methods: A structure-based virtual screening of ~250,000 compounds from the ZINC database was conducted to identify candidates targeting a predicted pocket within the HIF-1α C-TAD. Top hits were evaluated using molecular docking and 100 ns molecular dynamics simulations. The lead compound, HFS764, was further characterized using in silico absorption, distribution, metabolism, excretion, and toxicity (ADMET) profiling, homogeneous time-resolved fluorescence (HTRF) assays, and differential scanning fluorimetry (DSF). Functional effects were assessed in Caki-1 cells under hypoxia using hypoxia response element (HRE)-luciferase assays, cell viability and vascular endothelial growth factor (VEGF) secretion.Results: HFS764 demonstrated stable binding within the HIF-1α pocket, with ligand root-mean-square deviation (RMSD)